The quick-reference guide to sexuality & relationship counseling - Clinton, Timothy E.; Laaser, Mark R. (Grand Rapids Baker Book House, 2010)
One of the foremost counseling needs in our day is help with sexuality and relationship issues. But sometimes those who are faced with helping the hurting could use a little more information about the problems that people bring to them. The Quick-Refere
Keywords: Sex -- Religious aspects -- Christianity -- Handbooks, manuals, etc. Pastoral counseling -- Handbooks, manuals, etc. Counseling -- Handbooks, manuals, etc